Non-insulin anti-diabetic drugs: An update on pharmacological interactions. (January 2017) - Ruscica, M.; Baldessin, L.; Boccia, D.; Racagni, G.; Mitro, N.
Graphical abstract: Abstract: Nowadays, the goal in the management of type 2 diabetes mellitus (T2DM) remains personalized control of glucose. Since less than 50% of patients with T2DM achieve glycemic treatment goal and most of them take medications for comorbidities associated to T2DM, drug interactions, namely pharmacokinetic and pharmacodynamic interactions, may enhance or reduce the effect of compounds involved in hyperglycemia. Hence, clinicians should be aware of the severe complications in T2DM patients in case of a concomitant use of these medications. It is within this context that this review aims to evaluate the effect of a second drug on the pharmacokinetic of these compounds which may lead, along with several pharmacodynamic interactions, to severe clinical complications, i.e., hypoglycemia. Available drugs already approved in Europe, USA and Japan have been included.